The Effect of Using Information and Communication Technology to Improving the Quality of Blended Learning Elements’, a Survey Study at the Technical College of Management /Baghdad - Ibrahim, Bushra Abed; Hasan, Baydda Flayyih (Journal of Economics and Administrative Sciences, 2021)
The research has been based on two main variables (information and communication technology) and the quality of blended education (physical and electronic), aiming to reveal the relationship between four dimensions (physical devices, software, databases, communication networks) and the elements of education represented by (the teacher, the student, the teaching process, curriculum). The methodology and post-analysis-based research were conducted at the Technical College of Management / Baghdad through polling the opinions of a random sample that included (80) teachers out of (86) and the number of students (276) representing a random sample from all departments of the college (for the morning study) out of (3500) student. Tools for analysis and non-parametric statistical processing such as (arithmetic mean, standard deviation, relative importance) have been used to find out the perception of the sample members towards the research variables, and to test the validity of the hypotheses. The SPSS statistical analysis program of 2016 issuance has been used to test the correlation relationship and the impact among the main and sub-variables of the research. Finally, it has been concluded from the research that there is a correlation and influence between information and communication technology and the quality of education elements